2006
DOI: 10.1038/sj.ejcn.1602377
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chronic consumption of red wine polyphenols on vascular function in postmenopausal women

Abstract: Objective: To elucidate whether the chronic consumption of dealcoholised red wine (DRW) (polyphenol-rich component) and/ or red wine (RW) improves vascular function in hypercholesterolaemic postmenopausal women. Design, subjects and intervention: A randomised parallel-arm study. Forty-five hypercholesterolaemic postmenopausal women were randomised into either water, DRW or RW group for 6 weeks following a 4 week washout. Fasting measures of central haemodynamic parameters, arterial wave reflection and endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 35 publications
(38 reference statements)
0
25
0
2
Order By: Relevance
“…Such benefits were not observed when more than five glasses of wine were consumed at once (binge drinking), a level at which alcohol may become toxic (Hijmering et al 2007). Another study found dealcoholized red wine to be more effective than regular red wine (Agewall et al 2000), but there are data that contradict these results (Boban et al 2006, Naissides et al 2006b). …”
Section: Dose/effect a Finding Referencementioning
confidence: 63%
“…Such benefits were not observed when more than five glasses of wine were consumed at once (binge drinking), a level at which alcohol may become toxic (Hijmering et al 2007). Another study found dealcoholized red wine to be more effective than regular red wine (Agewall et al 2000), but there are data that contradict these results (Boban et al 2006, Naissides et al 2006b). …”
Section: Dose/effect a Finding Referencementioning
confidence: 63%
“…Indeed, some promising preliminary data suggest that lifetime fruit and vegetable consumption [Aatola et al 2010] but also dietary intervention with polyphenols-rich sources [Dohadwala et al 2011;Grassi et al 2009;Naissides et al 2006;Pase et al 2011;Vlachopoulos et al 2005] may provide an effective means of reducing arterial stiffness. However, long-term standardized studies dedicated to examine the role of polyphenols in the management of arterial stiffness, assessed by the noninvasive measure of pulse wave velocity (PWV), are highly recommended [Laurent et al 2006].…”
Section: Resultsmentioning
confidence: 99%
“…No significant correlation, however, was observed for other flavonoids [77]. De-alcoholised red wine, but not normal red wine, was able to reduce arterial stiffness in hypercholesterolemic post-menopausal women [78]. This indicates that PPs are beneficial to this condition, but the benefit is negated by alcohol.…”
Section: Human Trials Demonstrating Benefits Of Dietary Polyphenolicsmentioning
confidence: 94%